Convergence of solutions of variation inequalities with bilateral obstacles in perforated regions - Kovalevsky , A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Conditions and the type of convergence of the solutions of elliptical variational inequalities with two-sided obstructions in perforated regions are established.